Revisiting cytomegalovirus in pediatric allogeneic hematopoietic stem cell transplant recipients: current strategies for prevention and management in the letermovir era - Hiskey, Lisa; Hijano, Diego R.; Zakhour, Ramia (Frontiers in Pediatrics, 2025)
CMV infection remains the most common clinically significant infection in pediatric allogeneic hematopoietic stem cell (HCT) recipients, with seropositive recipients of transplants from seronegative donors at the highest risk for complications. In recent years, letermovir, a novel antiviral with a favorable toxicity profile, was approved first for adults and more recently for pediatric patients for the primary prophylaxis of CMV infection and disease in high-risk HCT recipients. Growing evidence from real-life data regarding the safety and efficacy of letermovir has transformed the landscape of CMV disease in HCT transplant recipients and led to a paradigm shift from a preemptive approach to prophylaxis. Other novel additions to the diagnosis, risk stratification, and treatment of CMV include the measurement of CMV-specific cellular-mediated immunity and the approval of maribavir as a treatment option for resistant/refractory CMV infection and disease. Other prevention and treatment modalities currently under development include virus-specific T cells, monoclonal antibodies, and vaccines. Despite these promising advancements, additional pediatric-specific studies are needed to better understand the viral and immunological implications of these novel preventive and therapeutic methods in this patient population.